(untitled) (Fiep Bulletin - online, 2024)
Introduction: Handball is a collective sports game (JDC) of cooperation-opposition, in which two teams face each other in a common space, competing for the ball simultaneously. objective: The objective of this work was to understand the manifestation of the technical skills of handball players from the Desportivo Matchedje club in Maputo. Methodology: This is a cross-sectional and quantitative descriptive study, composed of 16 female youth and junior handball players, aged between 15.63 ± 2.09 years. Anthropometric measurements (height and body mass) were evaluated, on the other hand, handball techniques were evaluated applying a battery of tests proposed by Bastos (2010). To compare means between the two groups, the t test was used. Student for independent variables with a significance level of 0.05 using the statistical package Microsoft Excel version 2019. Results: No statistically significant differences were evident in both groups in all anthropometric measurements P > 0.05. Regarding technical skills, the results obtained on average, Juvenile handball players present higher values ​​compared to Juniors in the 9-meter shot tests and the passing accuracy test. However, there were no statistically significant differences in both groups (P > 0.05). On the other hand, statistically significant differences (P < 0.05) were evident in the following tests: dribbling speed; speed of passing and dribbling, shooting, the Junior handball players presenting results compared to the Youth women. Conclusion: The study allowed us to observe differences in the mastery of technical skills of young athletes considering the level of competitive category.